Endothelin-1 increases superoxide production in human coronary artery bypass grafts - Cerrato, R; Cunnington, C; Crabtree, M; Antoniades, C; Pernow, J; Channon, K; Bohm, F (2012)
Aims: Endothelin-1 (ET-1) has been shown to increase endothelial superoxide (O2-) production in experimental animal models. It is unclear whether ET-1 increases O2- production in humans. We sought to elucidate whether ET-1 increases O2- production in human vessels and to identify the mechanism behind this effect. Main methods: Segments of internal mammary artery (IMA) and human saphenous vein (HSV) were harvested from 90 patients undergoing elective coronary artery bypass graft surgery. Paired vessel rings were incubated in the presence and absence of ET-1 (10- 10 M), the ETA receptor antagonist BQ123 alone, or in combination with the ETB receptor antagonist BQ788 (dual BQ) and known inhibitors of sources of O2- and further analysed for O2- production using lucigenin-enhanced chemiluminescence and DHE fluorescence. Key findings: ET-1 increased O2- production in both IMA (2.6 ± 1.5 vs. 1.4 ± 0.8 relative light units/s/mg tissue (RLU); n = 33; p < 0.0001) and HSV (1.4 ± 0.8 vs. 1.1 ± 0.6 RLU; n = 24; p < 0.05). The increase in O2- production induced by ET-1 in IMA was inhibited by co-incubation with dual BQ (p < 0.05; n = 15) and BQ123 (p < 0.05; n = 17). Of known O2- inhibitors, only incubation with Tiron and diphenyleneiodonium resulted in a significant reduction in ET-mediated O2- production. Significance: ET-1 increases O2- production especially in human arteries and less so in veins from patients with coronary artery disease via a receptor-dependent pathway involving a flavin dependent enzyme which is likely to be NADPH oxidase. Production of O2- may be an important factor underlying the negative effects of ET-1 on vascular function such as impairment of endothelium-dependent vasodilatation and pro-inflammatory effects. © 2012 Elsevier Inc. All rights reserved.